2019
DOI: 10.1371/journal.pone.0220490
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in platelet bioenergetics in Group 2 PH-HFpEF patients

Abstract: Background Pulmonary hypertension (PH) is characterized by elevated pulmonary artery pressure but classified into subgroups based on disease etiology. It is established that systemic bioenergetic dysfunction contributes to the pathogenesis of pulmonary arterial hypertension classified as World Health Organization (WHO) Group 1. Consistent with this, we previously showed that platelets from Group 1 PH patients demonstrate increased glycolysis and enhanced maximal capacity for oxidative phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…On the other hand, Nguyen et al recently observed that the platelets of patients with pulmonary hypertension secondary to left heart diseases demonstrated an enhanced maximal respiratory capacity despite a normal basal oxygen consumption rate [45]. Increased fatty acid oxidation, together with the metabolic syndrome, likely contributed to this result.…”
Section: Platelets' Mitochondrial Respiratory Chain Activity In Cardimentioning
confidence: 99%
“…On the other hand, Nguyen et al recently observed that the platelets of patients with pulmonary hypertension secondary to left heart diseases demonstrated an enhanced maximal respiratory capacity despite a normal basal oxygen consumption rate [45]. Increased fatty acid oxidation, together with the metabolic syndrome, likely contributed to this result.…”
Section: Platelets' Mitochondrial Respiratory Chain Activity In Cardimentioning
confidence: 99%
“…Unlike platelets from PAH patients, only an increase in maximal respiratory capacity, but not in glycolytic rate, was observed in platelets from PH-HFpEF patients relative to healthy controls. The enhancement of platelet maximal respiratory capacity was found to be associated with RV dysfunction, but not with mPAP or PVR in patients with PH-HFpEF ( 88 ). Whether or not a measurement of these factors can provide a method for distinguishing PH-LHD patient phenotypes, identifying at-risk subjects, and predicting PH-LHD patient outcomes requires additional research.…”
Section: Future Candidate Biomarkersmentioning
confidence: 95%
“…While this led the authors to conclude that high CRP levels may identify a unique HFpEF phenotype that is associated with comorbidity-driven systemic inflammation, CRP levels were not associated with PH or LV function in this study cohort ( 87 ). Lastly, platelets from patients with PH-HFpEF have also been shown to exhibit a distinct metabolic phenotype compared to patients with PAH ( 88 ). Unlike platelets from PAH patients, only an increase in maximal respiratory capacity, but not in glycolytic rate, was observed in platelets from PH-HFpEF patients relative to healthy controls.…”
Section: Future Candidate Biomarkersmentioning
confidence: 99%
“…Whether mitochondrial dysregulation takes place in other PH forms is unknown, as well as the role of the mitochondria in PH-LHD. However, alterations in platelet bioenergetics, a known proxy of mitochondrial function changes, have been recently reported in PH-LHD [65]. These alterations are characterized by an increase in respiratory capacity, similar to PAH subjects, but not by an increase in glycolysis.…”
Section: The Molecular Pathways Of Ph-lhdmentioning
confidence: 99%
“…These alterations are characterized by an increase in respiratory capacity, similar to PAH subjects, but not by an increase in glycolysis. Further, nitrite has shown no effect on the mitochondrial respiration of platelets [65].…”
Section: The Molecular Pathways Of Ph-lhdmentioning
confidence: 99%